2003
DOI: 10.1051/rnd:2003011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rabbit line on a program of cryopreserved embryos by vitrification

Abstract: -The aim of this study was to assess the application of a cryopreservation program to preserve two selected rabbit lines. One of them was selected by litter size at weaning, line V (Synthetic breed). The second, line R (synthetic breed), was selected by growth rate. In this study, embryos were collected, from donor does belonging to the 7th and 15th generations of lines R and V, respectively, were vitrified and were stored from 1992-1993. Those embryos from donor does belonging to the 17th and 21st generations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
2
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 19 publications
(19 reference statements)
6
32
2
5
Order By: Relevance
“…The effect of the genotype on the rederivation efficiency of cryobanked embryos in the rat, mouse, and rabbit has been observed [3,[12][13][14]. In fact, Vicente et al [15] reported that cryopreserved embryos from paternal rabbit lines (selected for growth characteristics) showed reduced survival rate after transfer (10% less) compared with cryopreserved em-bryos from maternal lines (selected for reproductive char-acteristics such as litter size at birth or at weaning). One management tool used to achieve higher survival rates after thawing consists of transferring the embryos of paternal lines to recipient does from a maternal line.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the genotype on the rederivation efficiency of cryobanked embryos in the rat, mouse, and rabbit has been observed [3,[12][13][14]. In fact, Vicente et al [15] reported that cryopreserved embryos from paternal rabbit lines (selected for growth characteristics) showed reduced survival rate after transfer (10% less) compared with cryopreserved em-bryos from maternal lines (selected for reproductive char-acteristics such as litter size at birth or at weaning). One management tool used to achieve higher survival rates after thawing consists of transferring the embryos of paternal lines to recipient does from a maternal line.…”
Section: Introductionmentioning
confidence: 99%
“…When line R does are induced to ovulate with GnRH analogues, no significant failures are observed in ovulation frequency: between 95-100% of AI females treated with a GnRH analogue ovulated (Viudes-de-Castro et al, 1995;Mehaisen et al, 2004;Vicente et al, 2003Vicente et al, :2012. Additionally, the GnRH analogue injected after AI could increase systemic LH blood concentrations and could promote more LH receptors in the follicles than GnRH naturally secreted after natural mating (Pieper et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, paternal rabbit lines selected uniquely for growth rate are characterised by elevated growth rate and adult live weight , but reduced reproductive performance (Mehaisen et al, 2004;Vicente et al, 2012). In previous studies comparing paternal and maternal rabbit lines, differences have been reported in ovulation frequency, ovulation rate, prenatal survival, gestational losses and consequently in litter size (Vicente et al, 2003;. Specifically, works carried out with line R, selected by weight daily gain, reported severe reproductive characteristics.…”
Section: Effects Of Selection By Growth Rate On Reproductive Performancementioning
confidence: 99%
See 2 more Smart Citations